Factors Affecting Consumer Responses to Influencer Marketing Campaigns - Azhar, Sarah Aida; Mohd Yusof, Yuslina Liza; Harun, Zatul Fahany (Information Management and Business Review, 2024)
In Malaysia, the emergence of influencers on social media has significantly influenced consumer behavior as many people connect and look up to these digital personalities. This study aims to investigate how factors such as trustworthiness, expertise, attractiveness, respect and likeness influence consumer responses to influencer marketing campaigns. Specifically, the research objectives are to examine the relationships between each of these factors and consumer responses and to determine whether consumer attitudes influence these relationships. In addition, the TEARS model appears to be more appropriate for this study than Ohanian’s (1990) source of credibility model because it incorporates characteristics of respect and similarity that align well with Eastern cultural norms. Respect and similarity are particularly important in Eastern societies where social harmony and collective values are emphasized. The TEARS model therefore provides a more comprehensive framework for understanding the impact of influencer endorsements in this cultural context. For this empirical study, data was collected from Shah Alam consumers aged 20-40 years old who own TikTok accounts and follow TikTok influencers who share and endorse products on the TikTok platform. Data was collected from 250 people, 200 of whom were classified as valid respondents. The survey was published online and the data was collected by the researcher using Google Forms. The links to the Google Forms survey were shared on social media such as Facebook, Instagram and WhatsApp. By focusing on these dimensions, the study fills research gaps by analyzing how these factors interact within influencer marketing, especially in an Eastern cultural setting.